The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10643-010-0407-z
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Transitioning Preschoolers with Autism Spectrum Disorders to Kindergarten

Abstract: In recent years, there has been a rapid increase in the number of children diagnosed with autism spectrum disorders (ASD), worldwide. Since children with ASD have limited social interaction and communication skills, they tend to lag behind their peers without disabilities in many areas. In particular, they are unable to easily transition smoothly from one stage of their life to another. Transitions from preschool settings to kindergarten and beyond should be a critical issue of concern for educators and parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 17 publications
1
23
0
1
Order By: Relevance
“…Children with developmental delays or disabilities may require supplemental supports as they transition to kindergarten due to their special needs. In particular, children with autism spectrum disorders (ASD), given their significant deficits in communication and social functioning, may require more comprehensive transition supports than other children (Denkyirah and Agbeke 2010;Forest et al 2004); however, there is limited research investigating the transition to kindergarten for children with disabilities. Furthermore, there are no known studies that compare transition practices across various diagnostic groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with developmental delays or disabilities may require supplemental supports as they transition to kindergarten due to their special needs. In particular, children with autism spectrum disorders (ASD), given their significant deficits in communication and social functioning, may require more comprehensive transition supports than other children (Denkyirah and Agbeke 2010;Forest et al 2004); however, there is limited research investigating the transition to kindergarten for children with disabilities. Furthermore, there are no known studies that compare transition practices across various diagnostic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although nearly all transition practices were identified by teachers as important, fewer practices were implemented (Forest et al 2004). Denkyirah and Agbeke (2010) surveyed preschool teachers in Ghana and the United States and asked teachers to endorse transition preparation practices that they viewed as important for supporting students with autism. Similar to the findings of Fowler et al, Denkyirah and Agbeke reported that all practices on the survey were important, with practices initiated early and involving multiple stakeholders (preschool, family, elementary school) as essential.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers thought that parental awareness about ASD was low. Denkyirah and Agbeke [] explored opinions of 65 preschool teachers from Ghana and 210 preschool teachers from the United States to assess characteristics of successful transition from preschool to kindergarten for children with ASD, identifying many similarities, and few dissimilarities between the two countries.…”
Section: Professional Knowledgementioning
confidence: 99%
“…Only two previous studies regarding ASD in Sub-Saharan Africa have been identified which have even tangentially considered teacher's professional knowledge. Denkyirah and Agbeke (2010) surveyed preschool teachers from Ghana alongside their counterparts from the USA concerning transition strategies for pupils with ASD; this study did not, however, investigate teachers' knowledge about the condition. Audu and Egbochuko (2011) surveyed 131 primary teachers from Benin City in Edo State, Nigeria, regarding their knowledge about ASD, and found that only 23% of them believed that ASD existed within Edo State, suggesting a low level of awareness.…”
Section: Teachers' Knowledge Regarding Asdmentioning
confidence: 99%